KNOWLEDGE, PRACTICE REGARDING NUTRITION CARE AND SOME RELATED FACTORS AMONG PREGNANT AND POSTPARTUM WOMEN IN YEN BINH AND BAO AI COMMUNE, LAO CAI PROVINCE 20250 (Vietnam Journal of Community Medicine, 2026)
Objective "To describe the status of knowledge and practice regarding nutrition care and to determine some associated factors among pregnant and postpartum women in Yen Binh and Bao Ai Commune, Lao Cai Province in 2025."Study Subjects and Methods: The study subjects are 248 pregnant women and mothers nursing children aged 1-3 months. The study is a descriptive cross-sectional design, conducted through interviews in April and May 2025.Results: "The overall level of knowledge regarding nutrition care reached 22.98%. Specifically, the percentage of mothers with correct knowledge about the role of energy-supplying nutrients and micronutrients was 52.1%, while this rate for iron supplementation was 45.1%. Regarding knowledge of macronutrients, the correct knowledge rate for protein was 43.5% and for fat was 36.2%. In practice, the overall level of correct practice reached 34.3%, with 65.7% not meeting the standard. The percentage of mothers with correct practice regarding carbohydrate supplementation during the first and third trimesters was 23.7% and 26.2%, respectively. The correct practice rate for protein supplementation during the first and third trimesters was 20.9% and 17.7%, respectively. The study also demonstrated an association between knowledge and practice concerning nutrition care and the mothers' educational level, with p < 0.05."Conclusions: The knowledge and practice regarding nutrition care among pregnant and postpartum mothers is limited. This finding is associated with the mothers' educational level, particularly those who have completed high school (upper secondary school) or higher. It is essential to continuously intensify communication, counseling, and guidance activities for mothers concerning nutrition care knowledge and practice skills to improve the health outcomes for both mothers and children.
Keywords: Knowledge, Practice, Pregnant women, Postpartum women